Development Of An Expert System For Identifying Dental Diseases Using Certainty Factor Method (Case Study : UPT Puskesmas Parmaksian) - Sirait, Gian Patar P.; Refisis, Nice Rejoice (Journal of Informatics and Data Science, 2024)
Dental health is crucial for human well-being, yet awareness of its significance is often low. This study addresses the need for an expert system to identify dental diseases, employing the Certainty Factor method. This method allows the system to express the level of certainty in expert statements, facilitating personalized use. The developed expert system calculates Certainty Factor values for each symptom, resulting in an 83% accuracy rate in identifying dental diseases based on tests conducted with 47 out of 56 cases. This research contributes to the field by providing an effective tool for dental disease identification, enhancing both awareness and practical applications in oral health.